2022
DOI: 10.3390/su142416958
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Nutritional Pattern Related to Maturation and Development

Abstract: In order to better understand the implications of physical activity and nutrition in child development, we conducted the present narrative with the aim to analyze the physical activity and nutritional patterns related to maturation and development. To reach our study objective, a consensus and critical review were conducted by analyzing primary sources such as academic research and secondary sources such as databases, web pages, and bibliographic indexes following procedures of previous critical narrative revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 194 publications
0
16
0
Order By: Relevance
“…Hogan et al, [ 20 ] reported that physical fitness and acute exercise could improve cognition by increasing the functionality of the attentional system in adolescence. Attention, an aspect of cognition, has also been reported to be closely linked to aerobic fitness throughout the human lifespan [ 21 , 22 ]. Furthermore, PA improves attention through increased release of transmitters involved in cognitive processes [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hogan et al, [ 20 ] reported that physical fitness and acute exercise could improve cognition by increasing the functionality of the attentional system in adolescence. Attention, an aspect of cognition, has also been reported to be closely linked to aerobic fitness throughout the human lifespan [ 21 , 22 ]. Furthermore, PA improves attention through increased release of transmitters involved in cognitive processes [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Attention, an aspect of cognition, has also been reported to be closely linked to aerobic fitness throughout the human lifespan [ 21 , 22 ]. Furthermore, PA improves attention through increased release of transmitters involved in cognitive processes [ 22 ]. Thus, low fitness levels appear to be correlated with poorer cognitive skills [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the benefits and implications of physical activity and health in physiological and psychological areas [ 301 , 302 , 303 , 304 , 305 , 306 , 307 , 308 , 309 ], many practical applications are proposed. There are some more important factors to take into account: Enhancing cognitive function through exercise: Given the demonstrated neurobiological impact of physical activity on the brain, particularly the hippocampus, training regimes can be scientifically tailored to enhance cognitive functions.…”
Section: Practical Applicationsmentioning
confidence: 99%
“…Children who possess superior physical performance also achieve more academic success [ 3 , 18 , 19 ]. Furthermore, physical activity is known to improve attention through release of transmitters involved in cognitive processes [ 20 ]. Thus, low physical activity or physical fitness levels appear to be correlated with poorer cognitive skills [ 21 ].…”
Section: Introductionmentioning
confidence: 99%